The Effect of Options on Stock Prices: 1973 to 1995 - Sorescu, Sorin M. (Journal of Finance, 2000)
I show that the effect of option introductions on underlying stock prices is best described by a two‐regime switching means model whose optimal switch date occurs in 1981. In accordance with previous studies, I find positive abnormal returns for options listed during 1973 to 1980. By contrast, I find negative abnormal returns for options listed in 1981 and later. Possible causes for this switch include the introduction of index options in 1982, the implementation of regulatory changes in 1981, and the possibility that options expedite the dissemination of negative information.